Social Cohesion through Social Media as Part of Disaster Information System in Disaster Prone Area - Puji Lestari; Eko Teguh Paripurno; Hikmat Surbakti (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2021)
Social media is one of the disaster communication means for social cohesion in information retrieval. However, Karo Regency has limitedly use WhatsApp, Instagram, and Facebook. This study aimed to evaluate social media Instagram and Facebook as part of the disaster information system in disaster-prone areas to improve social cohesion in Karo Regency, North Sumatra, Indonesia. This study combined qualitative and quantitative evaluation. Qualitative evaluation steps consist of (1) setting goals; (2) classification; (3) stating structured goals; (4) collecting data; (5) analyzing results of observations and measurements. Based on the evaluation, Instagram has been inactive since April 1, 2020, and Facebook has been inactive on August 17, 2017, due to the absence of competent human resources (HR). The use of internal WhatsApp groups is due to the unpreparedness in dealing with public comments. Based on a survey in early June 2021 to the Karo community showed that 56.3% of respondents were familiar with the Karo BPBD social media. The trust level of social media users for social cohesion in the disaster-prone area of Karo Regency was very high at 56.3%. Respondents believed that information conveyed through social media uploads is able to improve social cohesion in dealing with various disasters. This is formed because of the sense of belonging, social trust, generalized reciprocity, and social harmony. This study contributed in the form of BPBD policies in managing social media as an information system to improve social cohesion in the disaster-prone area ofKaro Regency. The new findings theoretically added caring in Johnson's Social Cohesion Theory.